How Can a Technology Enhanced Learning Environment Support Learning-Oriented Assessment in Higher Education? - Greenspon, Rasa; Volungevičienė, Airina (Pedagogika, 2023)
This study uses a qualitative approach to explore how technology enhanced learning (TEL) contributes to learning-oriented assessment (LOA). The analysis of 9 interviews revealed that a TEL environment may facilitate learning through enabling timely feedback, tracking learning progress, offering innovative and learner-centered assessment methods, and increasing transparency. However, due to a lack of digital assessment competences, teachers may face challenges designing LOA in a TEL environment.